Implementation of foreign refugee handling policy at the Kupang city national and political unity agency - Patrick Andryani Dondu; David Pandie; Melkisedek Neolaka (Trigin Publisher, 2023)
Indonesia is a country that has to deal with the problem of refugees from abroad entering and living in Indonesian territory. Indonesia is a stopover from waves of refugees to destination countries (asylum countries), namely Australia, America, Canada and others. Indonesia seems to really understand that human rights and humanitarian issues which are currently challenging international interactions need to get serious focus so that Indonesia seeks to provide protection for refugees from abroad who come to Indonesia. In this case, the State's obligation to protect, protect and uphold human rights is not only aimed at Indonesian citizens, but also includes citizens from other countries in Indonesia's territory, whether they are legally or illegally. In terms of international law, the State of Indonesia has no obligation to protect cross-border refugees due to the refusal of the State of Indonesia to sign the Vienna Convention on the status of refugees (the 1951 UN refugee convention). Therefore, in order to respect the Human Rights of Refugees, the Government of Indonesia is committed to enacting Presidential Regulation Number 125 of 2016 concerning Handling Refugees from Abroad, so that the Government has a reference standard for dealing with overseas refugees. Article 2 of the Presidential Regulation of the Republic of Indonesia Number 125 of 2016 states quite clearly that the handling of refugees is carried out based on cooperation between the central government and the United Nations through the High Commissioner for Refugees in Indonesia and/or organizationsinternational affairs in the field of migration or in the humanitarian field which has an agreement with the central government. The regulation broadly mandates 3 (three) government agencies and 1 (one) international organization to manage refugees, namely the Central Government which coordinates with the Regional Government in terms of accommodation, the Police in terms of security, Immigration in terms ofmonitoring and IOM as a facilitator of the basic needs of refugees.